Sulfur Stable Isotope Discrimination in Rice: A Sulfur Isotope Mass Balance Study - Cavallaro, Viviana; Maghrebi, Moez; Caschetto, Mariachiara; Sacchi, Gian Attilio; Nocito, Fabio Francesco (Frontiers in Plant Science, 2022)
The use of sulfur (S) stable isotopes to study S metabolism in plants is still limited by the relatively small number of studies. It is generally accepted that little S stable isotope discrimination occurs during SO42- uptake. However, S metabolism and allocation are expected to produce separations of S stable isotopes among the different plant S pools and organs. In this study, we measured the S isotope composition of the main S pools of rice plants grown under different SO42- availabilities in appropriate closed and open hydroponic-plant systems. The main results indicate that fractionation against 34S occurred during SO42- uptake. Fractionation was dependent on the amount of residual SO42- in the solution, showing a biphasic behavior related to the relative expression of two SO42- transporter genes (OsSULTR1;1 and OsSULTR1;2) in the roots. S isotope separations among S pools and organs were also observed as the result of substantial S isotope fractionations and mixing effects occurring during SO42- assimilation and plant S partitioning. Since the S stable isotope separations conserve the memory of the physiological and metabolic activities that determined them, we here underline the potential of the 32S/34S analysis for detailed characterization of the metabolic and molecular processes involved in plant S nutrition and homeostasis.